Method for producing molding material mixtures and moldings thereof in the foundry industry, as well as a kit for use in this method and an apparatus for use in this method - Patents.com

JP7631418B2Active Publication Date: 2025-02-18HUTTENES-ALBERTUS CHEMISCHE WERKE GMBH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023096313
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-06-30
Filing Date
2023-06-12
Publication Date
2025-02-18
Estimated Expiration
2038-06-28

Smart Images

  • Figure 0007631418000008
    Figure 0007631418000008
  • Figure 0007631418000009
    Figure 0007631418000009
  • Figure 0007631418000010
    Figure 0007631418000010
Patent Text Reader

Abstract

To provide a method for producing a molding material mixture or for producing a molding material mixture and a molded body thereof, preferably casting molds or cores, for use in the casting industry.SOLUTION: The molding material mixture comprises a molding base material and a solution or dispersion comprising lithium-containing sodium silicate, the method comprising the steps of: (1) producing or providing a kit at least comprising as separate components: (K1) an aqueous solution or dispersion comprising sodium silicate and (K2a) a first sodium-silicate-free solution or dispersion comprising lithium ions dissolved in water and preferably (K2b) a second sodium-silicate-free solution or dispersion, preferably comprising lithium ions dissolved in water of a lower concentration than in component (K2a), and then (2) producing a mixture of the molding base material with a proportion of the component (K1) and with a proportion of the component (K2a) and also optionally with a proportion of the component (K2b). Also described is an aforementioned kit, in particular for use in the method according to the invention. Also specified is an installation for producing an intermediary solution or dispersion, comprising lithium-containing sodium silicate for use in the production of a molding material mixture or for the production of a molding material mixture and a molded body thereof.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a molding material mixture or for use in the foundry industry, for producing a molding material mixture and its shaped bodies, preferably molds or cores, the molding material mixture comprising a mould base material and a solution or dispersion comprising lithium-containing water glass, the method comprising the steps of (1) producing or providing a kit comprising at least the following as separate components: (K1) an aqueous solution or dispersion comprising water glass, and (K2a) a first water glass-free solution or dispersion comprising lithium ions dissolved in water, and also preferably (K2b) a second water glass-free solution or dispersion, preferably comprising lithium ions dissolved in water at a lower concentration than component (K2a), and then (2) producing a mixture of the mould base material with a part of component (K1) and with a part of component (K2a), optionally also with a part of component (K2b). The present invention further relates to said kit, more particularly for application in the method of the present invention. The present invention also relates to an apparatus for producing an intermediate solution or dispersion comprising lithium-containing water glass, for use in the production of a molding material mixture, or for producing a molding material mixture and its shaped bodies. [Background technology]

[0002] Molds consist essentially of a mold, or a mold and a core, which, once constructed, represent the inverse shape of the casting to be produced. These cores and molds are shaped bodies, generally consisting of a refractory mold base material, e.g., silica sand, and a suitable binder system, which gives the mold sufficient mechanical strength when it is removed from the mold. The refractory mold base material is preferably in particulate, free-flowing form, which (after being incorporated into the molding material mixture) can be introduced into a suitable hollow mold and compressed. The binder provides a tight cohesion between the particles of the mold base material, giving the mold the required mechanical stability.

[0003] The mould and the shaped bodies contained therein (which may also be moulds and cores) must meet various requirements: they must initially have sufficient strength and temperature stability to be able to accommodate the liquid metal in the hollow spaces formed by the casting (part) mould or moulds during the casting operation itself; after the start of the solidification process, the mechanical stability of the casting is then ensured by the solidified metal layer which develops along the walls of the mould. Then, under the effect of the heat generated by the metal, the material of the mold will decompose so as to lose its mechanical strength, thus causing the cancellation of the cohesion between the individual particles of the refractory material. In the ideal case, the mold will again decompose down to fine particles of the mold base material, which can be easily removed from the casting.

[0004] The moldings can be produced using both organic and inorganic binders, which can be cured in each case by cold or hot methods. The cold method is a method carried out substantially without heating the mold, which is generally used for the production of cores at ambient temperature or at a temperature resulting from any reaction. Curing is carried out, for example, by passing a gas through the molding material mixture to be cured, with the induction of a chemical reaction. In the case of the hot method, the molding material mixture after molding by a heated mold is heated to a sufficiently high temperature, for example, to drive off the solvent present in the binder and / or to initiate a chemical reaction that causes the binder to harden. However, the disadvantage of organic binders based on phenolic resins is that, independent of their composition, they decompose during casting, emitting small and sometimes significant amounts of harmful substances, such as benzene, toluene and xylene. Furthermore, casting of organic binders generally results in undesirable odor and smoke emissions. In some systems, undesirable emissions occur during the early stages of mold production and / or storage. For this reason, inorganic binders are increasingly being selected for use in the foundry industry, and there is high technical and economic interest in further improving the product properties of the resulting molded bodies, in particular the molds and cores.

[0005] Inorganic binders, especially those based on water glass, have been known for a long time. To harden water glass, there are three different methods available in particular: (i) the passage of a gas, e.g. CO2, air or a combination of both; (ii) the addition of a liquid or solid hardener, e.g. certain esters; and (iii) thermal hardening, e.g. in the hot box method or by e.g. microwave treatment. However, the use of inorganic binder systems is often associated with other typical drawbacks.

[0006] Thus, unless appropriate special measures are taken, moulded bodies produced from inorganic binders relatively frequently have low strength. This becomes particularly evident immediately after removal of the core or mould or moulded body from the mould. The strength at this point ("hot strength" or "instantaneous strength") is particularly important for reliable handling of the core or mould when removed from the mould. High "cold strength" (i.e. the strength after complete hardening of the core or mould) is also important, so that the desired castings can be produced as free of casting defects as possible. DE-A-2 652 421 describes a binder which consists of a solution of a mixture of potassium and / or sodium silicate with lithium silicate and which is suitable, for example, as a binder for foundry cores.

[0007] US Patent No. 4,347,890 describes a method for binding particulate materials, which includes mixing the particulate materials with a lithium ion-containing solution (according to Example 1, this is an aqueous solution of lithium silicate or lithium water glass), adding and mixing sodium silicate to this mixture, and finally molding the mixture and curing it by microwave irradiation. WO 2006 / 024540 includes in its description a method for producing a mold, in which a particulate metal oxide is incorporated into a water glass-based binder. WO 2014 / 202042 describes lithium-containing molding material mixtures based on inorganic binders for producing moulds and cores for metal casting. For example, the possibility of improving the storage stability of moulds or cores produced using such binders by the explicit addition of lithium-containing compounds to inorganic binders based on water glass is described. At the same time, said cores or moulds are said to have a high level of strength.

[0008] In industrial practice, it has been found that liquid inorganic binders with a portion of lithium ions, especially those based on water glass, can become unstable quite quickly, depending on the concentration of the lithium ions and the storage conditions (especially the storage temperature). For example, in the course of storage, after only a few days, this type of unstable binder can cause turbidity, for example as a result of gel formation, and / or solid precipitation, for example of carbonates and / or silicates, and thus become inhomogeneous or non-uniform. It has also been found that such turbidity in liquid lithium-containing inorganic binders, or precipitation of solids from liquid lithium-containing inorganic binders, is a drawback in the processing of these binders, and can cause problems in particular with pumps, filters and / or metering units, or other problems in the further processing stages. Thus, a high level of lithium ions and also an increase in temperature increases the unfavorable tendency of these liquid binders to instability. Therefore, a certain increase in lithium ion content in inorganic binder systems based on water glass is advantageous for realizing high stability, especially high storage stability, of cores or molds in foundry industry.However, on the other hand, such binders with high lithium ion content show relatively poor storage integrity. Summary of the Invention

[0009] It was therefore a primary object of the present invention to provide a method for producing molding material mixtures or for producing molding material mixtures and shaped bodies (e.g. moulds or cores), more particularly storage-stable shaped bodies for the foundry industry, in which the use of inorganic binders, in particular water glass, with a variably adjustable concentration, including a high concentration, of lithium ions depending on external parameters is possible, whereby the disadvantages of the prior art are reduced or avoided.

[0010] A further object of the present invention was to provide an easily manageable kit suitable for the preparation of liquid lithium-containing inorganic binders with variably adjustable lithium ion concentrations, which binders should in any case be stable under the respective storage conditions prior to the intended use. A further particular object of the present invention was to provide an apparatus, e.g. a production plant, by which the implementation of said process is possible also on an industrial production scale. The invention and inventive preferred combinations of preferred parameters, properties and / or components thereof are defined in the appended claims. Preferred embodiments of the invention are set forth or defined in the following description and in the examples.

[0011] Surprisingly, the main object of the present invention and also further objects and / or components are the inventive process for producing a molding material mixture or for producing a molding material mixture and its moldings, preferably storage-stable moldings, in which the molding material mixture (M1) Mold base material and (M2) has a SiO2 / M2O molar ratio in the range of 1.6 to 3.5, preferably in the range of 1.8 to 3.0; The mole fraction of Li2O in M2O is in the range of 0.05 to 0.60, preferably in the range of 0.1 to 0.4. Solution or dispersion containing lithium-containing water glass Including, Follow these steps: (1) The following separate components: (K1) the SiO content is in the range of 20 to 34% by weight, preferably in the range of 25 to 34% by weight, based on the total weight of the solution or dispersion, and / or the SiO / MO molar ratio is greater than the molar ratio of the lithium-containing water glass in the molding material mixture to be produced; an aqueous solution or dispersion containing water glass; and (K2a) The concentration of lithium ions is in the range of 0.3 to 5.3 mol / L, preferably in the range of 1.0 to 5.0 mol / L; The total concentration of lithium, sodium and potassium ions is in the range of 0.3 to 28.0 mol / L, preferably in the range of 0.3 to 20.0 mol / L, and more preferably in the range of 1.0 to 10.0 mol / L. A first water glass-free solution or dispersion containing lithium ions dissolved in water. Producing or providing a kit comprising at least And then (2) preparing a mixture of the mould base material (M1) with a part of component (K1) and also with a part of component (K2a), the solution or dispersion (M2) being formed by mixing together the components of the kit used; Including, M2O represents the total amount of lithium oxide, sodium oxide and potassium oxide in each case It has been found that this can be achieved by the method. Preferred according to the invention is the embodiment of the inventive process specified above, in which in component (K1) the SiO2 / M2O molar ratio is greater than the molar ratio of the lithium-containing waterglass in the molding material mixture produced.

[0012] Particular preference is given to the above-specified embodiment of the inventive process, in which component (K1) takes the form of an aqueous water-glass-containing solution or dispersion, the SiO2 content being in the range from 20 to 34% by weight, preferably in the range from 25 to 34% by weight, based on the total weight of the solution or dispersion, and the SiO2 / M2O molar ratio is greater than the molar ratio of the lithium-containing water-glass in the molding material mixture produced. The above-described methods of the present invention (more specifically, the methods of the present invention expressed as preferred in the text) in which the aqueous solution or dispersion containing water glass (K1) has a pH in the range of 10.0 to 13.0, preferably in the range of 11.0 to 12.5, are preferred. At the same time, the above-described inventive methods (more precisely, the inventive methods expressed as preferred in the text) are also suitable, in which the first water glass-free solution or dispersion (K2a) containing lithium ions dissolved in water has a pH in the range from 8.0 to 14.0, preferably in the range from 11.5 to 13.5.

[0013] In the context of the present invention, each of the following names shall have the definition set out below: "SiO2" represents the molar amount of silicon in an aqueous solution or dispersion calculated according to the empirical formula SiO2, independently of whether the silicon on which this calculation is based is actually present as SiO2 in the method of the invention (or in the kit of the invention). "M" represents an alkali metal selected from the group consisting of lithium, sodium and potassium. "M2O" represents the total molar amount of alkali metals in the aqueous solution or dispersion, calculated according to the empirical formula M2O. "Li2O" therefore represents the molar amount of lithium, calculated according to the empirical formula Li2O. These calculations are independent of whether the alkali metal on which the calculation is based in each case is actually present in the method of the invention (or in the kit of the invention) in the form "M2O".

[0014] In the above-specified method of the present invention, component (K1) comprises an aqueous (water-containing) solution or dispersion comprising water glass. Water glass in the context of the present invention is an alkali metal water glass known per se, which comprises vitreous, i.e. amorphous, water-soluble sodium silicates, potassium silicates and lithium silicates solidified from the melt, or aqueous solutions of said sodium, potassium and lithium silicates in low concentrations which do not affect the stability, in particular the storage stability, of the water glass. The mold base material (M1) is preferably a particulate refractory mold base material. In accordance with the ordinary understanding of those skilled in the art, "refractory" in this context refers to compositions, materials and minerals that can withstand at least a short time the temperature exposure involved in the casting and / or solidification of molten metal, e.g., aluminum. Examples of suitable mold base materials are silica sand, zircon or chromite sand, olivine, vermiculite, bauxite, chamotte, and synthetic mold base materials. The mold base material (M1) may also be a mixture of two or more (preferably particulate, refractory) substances.

[0015] The shaped bodies produced by the above-specified method of the present invention are preferably shaped bodies for use in the foundry industry, more preferably molds or cores. A particular advantage of the method of the present invention is the possibility of using binder systems, which have a high and / or variably adjustable lithium ion content, and which are not subject to the time restrictions on the storage period of known binders with a high (but generally not changeable and / or to be changed) lithium ion content, or are subject to a much smaller time restriction. Thus, by the method of the present invention, it is possible to produce shaped bodies that have high strength and can be stored for a relatively long period, preferably for a period ranging from 1 day to a maximum of 2 weeks, to a practically relevant extent, without loss of their advantageous properties. Thus, after their production and until their use in the foundry operation, the shaped bodies produced by the method of the present invention can be easily handled and / or stored for a relatively long period without deformation or fragmentation, thus making production from stock possible. A particular advantage is the property of the moulded bodies produced by the method of the invention, which maintains high strength and remains stable even at high humidity, so that the moulded bodies produced are distinguished by high storage stability even in humid or hot and humid climates, but also in temperate climates, where the method of the invention provides advantages in terms of changing weather conditions (seasons).

[0016] In the above-specified method of the invention, component (K2a) comprises lithium ions dissolved in water. If component (K2a) is a solution, the lithium ions are a constituent of the solution. If component (K2a) is a dispersion, the lithium ions are preferably present in the solution, at least predominantly and preferably completely in the continuous (liquid, aqueous) phase. In addition to the lithium ions, component (K2a) preferably comprises sodium ions and / or potassium ions as further alkali metal ions. Component (K2a) may comprise lithium ions and potassium ions, or component (K2a) may comprise lithium ions and sodium ions, or component (K2a) may comprise lithium ions, sodium ions and potassium ions. The maximum total concentration of lithium, sodium and potassium ions in component (K2a) depends on factors including the nature and proportion of the alkali metal ions present. The skilled person knows how to establish the necessary and / or preferred concentrations of alkali metal ions under the prevailing and / or desired conditions.

[0017] The kit produced or provided in step (1) comprises the following separate components: (K2b) The concentration of lithium ions is lower than that of component (K2a), preferably in the range of 0 to 5.0 mol / L, more preferably in the range of 0 to 2.0 mol / L; the total concentration of lithium, sodium and potassium ions is in the range of 0.3 to 28.0 mol / L, preferably in the range of 0.3 to 20.0 mol / L, and more preferably in the range of 1.0 to 10.0 mol / L; Preferably, the total concentration of lithium, sodium and potassium ions differs from the total concentration of lithium, sodium and potassium ions in component (K2a) by no more than 20%, preferably no more than 10%. A second waterglass-free solution or dispersion containing alkali metal ions dissolved in water, preferably containing lithium ions dissolved in water. Further comprising: Step (2) is as follows: (2) preparing a mixture of the mould base material (M1) with a part of component (K1) and also with a part of component (K2a), or a mixture which may also contain a part of component (K2b), and forming a solution or dispersion (M2) by mixing together the components of the kit used, Includes The methods of the invention described above (and more particularly those referred to as preferred below) are particularly preferred.

[0018] Preferred are the above inventive methods (more particularly the inventive methods referred to as preferred in the text) in which the second waterglass-free solution or dispersion (K2b) containing lithium ions dissolved in water has a pH in the range of 8.0 to 14.0, preferably in the range of 11.5 to 13.5. Regarding the preferred pH values ​​for the solutions or dispersions (K1) and / or (K2a), reference is made to the present disclosure given above.

[0019] Thus, the molding material mixture: (M1) Mold base material and (M2) has a SiO2 / M2O molar ratio in the range of 1.6 to 3.5, preferably in the range of 1.8 to 3.0; The mole fraction of Li2O in M2O is in the range of 0.05 to 0.60, preferably in the range of 0.1 to 0.4. Solution or dispersion containing lithium-containing water glass Including the following steps: (1) The following separate components: (K1) the SiO2 content is in the range of 20 to 34% by weight, preferably in the range of 25 to 34% by weight, based on the total weight of the solution or dispersion, and / or the SiO2 / MO molar ratio is greater than the molar ratio of the lithium-containing water glass in the molding material mixture to be produced; an aqueous solution or dispersion containing water glass; (K2a) The concentration of lithium ions is in the range of 0.3 to 5.3 mol / L, preferably in the range of 1.0 to 5.0 mol / L; The total concentration of lithium, sodium and potassium ions is in the range of 0.3 to 28.0 mol / L, preferably in the range of 0.3 to 20.0 mol / L, and more preferably in the range of 1.0 to 10.0 mol / L. a first water glass-free solution or dispersion comprising lithium ions dissolved in water; and (K2b) The concentration of lithium ions is lower than that of component (K2a), preferably in the range of 0 to 5.0 mol / L, more preferably in the range of 0 to 2.0 mol / L; the total concentration of lithium, sodium and potassium ions is in the range of 0.3 to 28.0 mol / L, preferably in the range of 0.3 to 20.0 mol / L, and more preferably in the range of 1.0 to 10.0 mol / L; Preferably, the total concentration of lithium, sodium and potassium ions differs from the total concentration of lithium, sodium and potassium ions in component (K2a) by no more than 20%, preferably no more than 10%. A second waterglass-free solution or dispersion containing alkali metal ions dissolved in water, preferably containing lithium ions dissolved in water. Producing or providing a kit comprising at least And then (2) preparing a mixture of the mould base material (M1) with a part of component (K1) and also with a part of component (K2a) and with a part of component (K2b), the solution or dispersion (M2) being formed by mixing together the components of the kit used; Including, MO represents in each case the total amount of lithium oxide, sodium oxide and potassium oxide; Particular preference is given to the process according to the invention for producing molding material mixtures or for producing molding material mixtures and moldings thereof, preferably storage-stable moldings.

[0020] In a particularly preferred method of the invention as shown above, component (K2b) comprises alkali metal ions, preferably lithium ions, sodium ions and / or potassium ions, dissolved in water. Component (K2b) preferably comprises lithium ions. The alkali metal ions in component (K2b) may comprise only lithium ions, or only sodium ions, or only potassium ions. Component (K2b) may also comprise lithium and sodium ions, or lithium and potassium ions, or sodium and potassium ions, as alkali metal ions. In a preferred embodiment of the method of the invention or of the preferred method according to the invention, the concentration of lithium ions in component (K2b) is lower than in component (K2a), preferably in the range of 0.1 to 5.0 mol / L, more preferably in the range of 0.1 to 2.0 mol / L.

[0021] An advantage of a preferred embodiment of the method of the present invention, where the total concentration of lithium, sodium and potassium ions in component (K2b) differs from the total concentration of lithium, sodium and potassium ions in component (K2a) by no more than 20%, preferably no more than 10%, is that when kit components (K1), (K2a) and (K2b) are mixed together (in the absence or presence of a mould base material (M1)), the total concentration of lithium, sodium and potassium ions in the resulting solution or dispersion (M2) is identical or at least similar to the total concentration of lithium, sodium and potassium ions in a solution or dispersion (M2) formed only by mixing together kit components (K1) and (K2a). Thus, when kit component (K2b) (having a lower lithium ion concentration than kit component (K2a)) is used in the method of the invention, the lithium ion concentration of the resulting solution or dispersion (M2) is affected, and is preferably lower, compared to a solution or dispersion (M2) prepared by mixing only kit components (K1) and (K2a) together under otherwise identical conditions.

[0022] Thus, kit component (K2b) can be advantageously used to reduce the lithium ion content of solution or dispersion (M2) in any manner different from what would occur by adding the amount of the corresponding kit component (K2a) without affecting or modifying other properties of the resulting solution or dispersion (M2), such as its SiO2 / M2O molar ratio or its total alkali metal ion concentration, in an easily scalable and well controllable manner, in a manner relevant for implementation. It is therefore possible to reduce the addition of (K2a) while ensuring that, as a result of the addition of component (K2b), the binder (M2) produced has the same ratio and the same concentration as before with a higher proportion of (K2a).

[0023] In step (2) of the preferred method of the invention shown above, a mixture is produced from a mould base material (M1) together with a part of component (K1) and also with a part of component (K2a) and possibly also with a part of component (K2b). In this case and below "optionally" means that a part of component (K2b) is used or not used, depending on the individual requirements. As a result, the desired lithium ion concentration can be individually and flexibly established in the solution or dispersion (M2). It is therefore possible to take into account the ambient conditions (especially humidity) when establishing the lithium ion content or concentration of the solution or dispersion (M2) and to add in each case only the amount of lithium ions necessary to optimise the production operation under the prevailing environmental conditions. One of the measures made possible by this flexible means of metering lithium ions when producing the solution or dispersion (M2) is the cost saving of raw materials for the expensive lithium compounds present in the kit components (K2a) and preferably also (K2b).

[0024] The mixtures specified above can be produced by first mixing a portion of component (K1) with the mold base material (M1), then mixing this premix with a portion of component (K2a) and optionally also with a portion of component (K2b) to obtain a molding material mixture; the amount of lithium ions in the molding material mixture is preferably established by the appropriate amount and lithium ion concentration of component (K2a), respectively, and may also be established by the selection of component (K2b). The premix is ​​mixed with a portion of component (K2a) and optionally also with a portion of component (K2b), which also results in the formation of a solution or dispersion (M2).

[0025] The mixture can also be produced by first mixing the mould base material (M1) with a part of component (K2a) and also with a part of component (K2b), and then mixing this premix with a part of component (K1) to obtain a moulding material mixture; the amount of lithium ions in the moulding material mixture is preferably established by the appropriate amount and lithium ion concentration, respectively, of component (K2a) and may also be established by the selection of component (K2b). Mixing the premix with a part of component (K1) also results in the formation of a solution or dispersion (M2).

[0026] The mixture of step (2) of the method of the present invention is preferably prepared by first mixing a portion of component (K1) with a portion of component (K2a) and optionally with a portion of component (K2b), thereby resulting in a solution or dispersion (M2), preferably the amount of lithium ions in the solution or dispersion (M2) being established by the selection of the appropriate amounts of components and lithium ion concentrations (K2a), respectively, and possibly also by the selection of component (K2b), and then this separately prepared solution or dispersion (M2) is mixed with the mould base material (M1).

[0027] Particularly preferably, the mixture of step (2) of the method of the invention is prepared by first mixing a portion of component (K2a) with a portion of component (K2b) to form a "(K2a)+(K2b) pre-mixture" and then mixing this "(K2a)+(K2b) pre-mixture" with a portion of component (K1) to give a solution or dispersion (M2), the amount of lithium ions in the solution or dispersion (M2) being preferably established by the selection of appropriate amounts of components (K2a) and (K2b), respectively, and the lithium ion concentration.

[0028] The molding material mixture is (M1) Mold base material and (M2) has a SiO2 / M2O molar ratio in the range of 1.6 to 3.5, preferably in the range of 1.8 to 3.0; The mole fraction of Li2O in M2O is in the range of 0.05 to 0.60, preferably in the range of 0.1 to 0.4. Solution or dispersion containing lithium-containing water glass Including, Follow these steps: (1) The following separate components: (K1) The SiO2 content is in the range of 20 to 34% by weight, preferably in the range of 25 to 34% by weight, based on the total weight of the solution or dispersion, and / or the SiO2 / MO molar ratio is greater than the molar ratio of the lithium-containing water glass in the molding material mixture to be produced. an aqueous solution or dispersion containing water glass; (K2a) The concentration of lithium ions is in the range of 0.3 to 5.3 mol / L, preferably in the range of 1.0 to 5.0 mol / L; The total concentration of lithium, sodium and potassium ions is in the range of 0.3 to 28.0 mol / L, preferably in the range of 0.3 to 20.0 mol / L, and more preferably in the range of 1.0 to 10.0 mol / L. A first water glass-free solution or dispersion containing lithium ions dissolved in water. and (K2b) The concentration of lithium ions is lower than that of component (K2a), preferably in the range of 0.1 to 5.0 mol / L, more preferably in the range of 0.1 to 2.0 mol / L; the total concentration of lithium, sodium and potassium ions is in the range of 0.3 to 28.0 mol / L, preferably in the range of 0.3 to 20.0 mol / L, and more preferably in the range of 1.0 to 10.0 mol / L; Preferably, the total concentration of lithium, sodium and potassium ions differs from the total concentration of lithium, sodium and potassium ions in component (K2a) by no more than 20%, preferably no more than 10%. A second water glass-free solution or dispersion containing lithium ions dissolved in water. Producing or providing a kit comprising at least And then (2) preparing a mixture of the mould base material (M1) with a part of component (K1) and also with a part of component (K2a) and with a part of component (K2b), the components of the kit to be used being mixed together to form a solution or dispersion (M2), Including, M2O represents the total amount of lithium oxide, sodium oxide and potassium oxide in each case Particular preference is given to the inventive process for producing molding material mixtures or for producing molding material mixtures and moldings thereof, preferably storage-stable moldings.

[0029] As indicated above or below, the method of the invention or preferred according to the invention is preferably such that in step (2), in the absence of a mould base material, a solution or dispersion (M2) is first formed by mixing together the components of the kit to be used, and then a mixture of the mould base material (M1) or a part of it with a part or the total amount of the resulting solution or dispersion (M2) is formed. The components of the kit used are mixed together in the usual manner, preferably by means of a stirring mechanism or mixing tube, preferably a static mixing pipe.

[0030] Thus, the preferred method variant (hereinafter also referred to as "premixing of the kit components to be used") is particularly advantageous, since it is possible to prepare a premixed solution or dispersion (M2) and then store it for a certain period of time and adapt (or make it adaptable) to ambient conditions, such that instability does not cause precipitation (due to precipitation of the components from the solution or dispersion (M2)) and / or gelation. A premixed solution or dispersion (M2) of this kind can also be used to feed automatic or semi-automatic production equipment, so that the premixed solution or dispersion (M2) can be used directly in a continuous or mainly continuous industrial production process.

[0031] In-house investigations have shown that in the case of solutions or dispersions (M2) (see below in this regard) or in the manufacture of shaped bodies using stored solutions or dispersions (M2) or in castings produced using shaped bodies produced with stored solutions or dispersions (M2), the solutions or dispersions (M2) produced as described above (premixed) can be stored - depending on the concentration and storage conditions (e.g. temperature, stirring) - for up to several weeks, preferably for up to 6 days, more preferably for up to 3 days, without observable quality defects.

[0032] It has further been found that the separate (unmixed) components (K1), (K2a) and (K2b) remain stable for extended periods, for example more than one year, unchanged or substantially unchanged on storage, without any performance-related quality degradation. Thus, a particular service provided by the present invention is that waterglass-containing binders with high lithium ion concentrations can be available for manufacturing or production on demand and can be used quickly, with a solution to the problems associated with the perishability and / or poor (short) shelf life of such waterglass-containing binders with high lithium ion concentrations. The prepared (premixed) solution or dispersion (M2) is preferably stored in a sealed container. In one particularly advantageous embodiment of the method of the invention, the above-mentioned methods (especially those identified as preferred above or below, preferably method variants which comprise a premixing of the kit components used) are preferred, in which the solution or dispersion (M2) produced does not contain any visible precipitates or gel parts before the mixture with the mould base material (M1) is formed.

[0033] In-house trials have shown that a test of the prepared solution or dispersion (M2) for visible precipitates or gel parts can be a convenient check. Thus, in practice, a person skilled in the art can recognize and determine with sufficient confidence whether the solution or dispersion (M2) has the required consistency or the necessary quality for further processing in the method of the present invention, step (2). For the purpose of producing a molding material mixture, said test is preferably carried out immediately before the mixture is produced from the mold base material (M1) with the prepared solution or dispersion (M2). If the test shows that the prepared solution or dispersion (M2) does not have the required quality or consistency for further processing, it is not used in the further method steps, but is instead preferably replaced by a different solution or dispersion (M2) that has the required quality or consistency for further processing. This design of the method allows a fast, convenient and cost-effective quality control to be carried out in the production operation. Also suitable are the above-mentioned inventive methods (especially the methods identified above or below, preferably method variants which comprise premixing of the components of the kit used) in which the components of the kit used are mixed together to form a solution or dispersion (M2) in a mixing facility, preferably the mixing facility being a metered vessel or a mixing tube, and more preferably a mixing tube, very preferably a static mixing pipe.

[0034] The mixing equipment may be separate, for example self-contained, mixing equipment, which are operated together and / or independently in the at least partially continuous production of shaped bodies ("batch operation"). Batch operation of this kind has the advantage that various batches of solution or dispersion (M2) can be produced at any time and their quality can be verified in each case. The mixing equipment may be a component of the at least partially continuous production of shaped bodies, for example a component of an apparatus for the at least partially continuous production of shaped bodies ("continuous or semi-continuous operation"). Continuous or semi-continuous operation of this kind is particularly suitable for the (industrially preferred) at least partially continuous production of relatively large numbers of shaped bodies, for example production from stock. The mixing equipment may be a stock vessel, in which at least one component (K1), (K2a) and / or (K2b) is stored or held for use in the at least partially continuous production of shaped bodies and, if necessary and if necessary, mixed with at least one complementary component (K1), (K2a) and also with (K2b).

[0035] The mixing equipment is preferably a metered vessel or a mixing tube. A preferred mixing tube is a static mixing pipe. A static mixing pipe is a mixing equipment and is particularly preferred for use in the method of the present invention. Static mixing pipes manufactured by Sulzer, types "CompaX" or "SMX" plus, are examples suitable for use in the method of the present invention. Preferred weighing vessels are selected from the group consisting of Intermediate Bulk Containers (identical to IBC or Schutz containers), drums and canisters. Preferred mixing equipment for said continuous or semi-continuous operation is a mixing tube, preferably a static mixing pipe. However, said weighing vessels can also be used in continuous or semi-continuous operation.

[0036] Also suitable are the above-mentioned methods of the invention (especially those identified as preferred above or below, preferably method variants which include premixing of the kit components used) in which a part or the total amount of the solution or dispersion (M2) formed is stored in the mixing facility for a period of not more than 7 days, preferably not more than 3 days, more preferably not more than 2 days, before forming a mixture with a part of the mould base material (M1). This counteracts the occurrence of precipitation (due to precipitation of components from the solution or dispersion (M2)) and / or gels.

[0037] If the mixing equipment (mixing tube or metering vessel) is a component of an at least partially continuous molding production, there is generally no provision for long-term storage of the produced solution or dispersion (M2), for example for a period of more than 2 days, preferably for a period of more than 1 day. Instead, in these cases, there is customarily provision for a relatively short storage, preferably less than 1 day, so that this type of at least partially continuous production or production process is possible. However, if the mixing equipment also serves as a stock vessel for the produced solution or dispersion (M2) before mixing with the mold base material (M1), long-term storage of the produced solution or dispersion (M2) (preferably for a period of less than 7 days as defined above) may be preferred.

[0038] Additional steps - establishing, determining or estimating one or more parameters selected from the group consisting of: ambient temperature during the production of the shaped body, relative humidity during the production of the shaped body, temperature during storage of the shaped body, relative humidity during storage of the shaped body, absolute humidity during the production of the shaped body, absolute humidity during storage of the shaped body, and storage time of the shaped body; and - controlling the proportions to be used of components (K2a) and (K2b) as a function of an established, determined or estimated parameter or parameters selected from the group consisting of the ambient temperature during the production of the shaped bodies, the relative humidity during the production of the shaped bodies, the temperature during the storage of the shaped bodies, the relative humidity during the storage of the shaped bodies, the absolute humidity during the production of the shaped bodies, the absolute humidity during the storage of the shaped bodies and the storage period of the shaped bodies. The above-mentioned inventive methods (especially those specified as preferred above or below) for producing molding material mixtures and moldings thereof which comprise Particularly preferred in this case are combinations of parameters from the group consisting of the ambient temperature during the production of the shaped bodies and the temperature during storage of the shaped bodies with the relative humidity during the production of the shaped bodies and the relative humidity during storage of the shaped bodies. "Relative humidity" in this case - in accordance with the usual understanding of those skilled in the art - denotes the actual percentage of water in the air at a given temperature, based on the maximum physical amount of water that air can contain at that temperature. Absolute humidity is determined - in accordance with the common understanding of those skilled in the art - from temperature and relative humidity. For example, if the temperature increases while the relative humidity remains the same, or if the relative humidity increases at constant temperature, a higher absolute humidity is achieved. Factors that make the establishment of a relatively high concentration of lithium ions appear practical in the process of the invention are, in particular, higher absolute humidity during the preparation and / or storage of the shaped bodies and / or longer storage periods of the shaped bodies.

[0039] Thus, preferably, a higher or lower lithium ion concentration is established in the solution or dispersion (M2) according to the established, determined or estimated parameter value. A higher lithium ion concentration can be established preferably by increasing the proportion of component (K2a) in the solution or dispersion (M2), for example by increasing the proportion of incorporation of component (K2a) and / or (if component (K2b) is used) by decreasing the proportion of incorporation of component (K2b). Depending on the requirements, component (K2b) can also be omitted completely.

[0040] The process is therefore carried out as an at least partially continuous, preferably mainly continuous, production of several shaped bodies, When one or more parameters selected from the group consisting of: ambient temperature during the production of the molded body, relative humidity during the production of the molded body, temperature during storage of the molded body, relative humidity during storage of the molded body, absolute humidity during the production of the molded body, absolute humidity during storage of the molded body, and storage time of the molded body are increased or expected to increase, - for the production of mouldings, the proportion of component (K2a) used is increased, and / or - Increasing the mole fraction of Li2O in MO in the solution or dispersion (M2) for the production of shaped bodies The methods of the invention described above (especially those identified above or below as preferred) are preferred.

[0041] Conversely, if one or more parameters selected from the group consisting of the ambient temperature during the production of the molded body, the relative humidity during the production of the molded body, the temperature during the storage of the molded body, the relative humidity during the storage of the molded body, the absolute humidity during the production of the molded body, the absolute humidity during the storage of the molded body, and the storage period of the molded body are decreased or decreased, or are expected to decrease or are expected to decrease, - reducing the proportion of component (K2a) used for the preparation of the shaped bodies and / or increasing the proportion of component (K2b) which may be used for the preparation of the shaped bodies, and / or - Reducing the mole fraction of Li2O in M2O in the solution or dispersion (M2) for the production of shaped bodies It is of course advantageous to design the method of the present invention in this way.

[0042] Likewise preferred are the methods of the invention described above (especially those identified as preferred above or below), in which data collection or processing equipment is provided for establishing, determining or estimating one or more parameters selected from the group consisting of: ambient temperature during the production of the shaped body, relative humidity during the production of the shaped body, temperature during storage of the shaped body, relative humidity during storage of the shaped body, absolute humidity during the production of the shaped body, absolute humidity during storage of the shaped body and storage time of the shaped body, and To control the proportions of components (K2a) and (K2b) to be used as a function of the established, determined or estimated parameter or parameters, a control facility is provided and preferably a data connection is set up between the data collection or processing facility and the control facility to transfer parameter data. The data collection or processing equipment is preferably an instrument for obtaining climatic conditions or a data logger. The control equipment is preferably an automatic mixing equipment. This said embodiment of the method of the invention has the advantage that the mixing or weighing of the kit components can be carried out using automation or at least partial automation as a function of influencing parameters in an industrial manufacturing operation.

[0043] During the preparation of the molding compound mixture, (M3) Particulate, amorphous silicon dioxide; barium sulfate; carbohydrates; phosphorus compounds; surface active compounds; boron oxide compounds; metal oxides; lubricants, esters and release agents. One or more components selected from the group consisting of The methods of the invention described above (especially those identified as preferred above or below) are also preferred.

[0044] The particulate amorphous silicon dioxide ("SiO2") used is preferably particulate amorphous silicon dioxide of normal purity, i.e. with normal impurities and secondary constituents. For the purposes of the present invention, it is preferred to use particulate amorphous silicon dioxide with a silicon dioxide content of at least 85% by weight, more preferably at least 90% by weight, and very preferably at least 95% by weight. The term "particulate" in this case refers to a solid powder (including dust) or alternatively a granular material that is preferably pourable and therefore also sieveable. The d90 based on the number of particles of the particulate amorphous silicon dioxide is preferably less than 100 μm, more preferably less than 45 μm. This means that 90% of the particles of the particulate amorphous silicon dioxide present in the molding material mixture are preferably smaller than 100 μm, more preferably smaller than 45 μm. The d90 is preferably determined by micrographs taken with a scanning electron microscope. The particulate amorphous silicon dioxide used may be synthetically produced or naturally occurring. The latter, known for example from DE 102007045649, are not preferred as they often contain a certain degree of crystalline fraction and are therefore classified as carcinogenic. Synthetically produced particulate amorphous silicon dioxide is produced by carefully carried out chemical reactions. Such examples are the flame hydrolysis of silicon tetrachloride and the reduction of silica sand with coke in an arc oven in the production of silicon and ferrosilicon. Amorphous SiO2 produced by these two methods is also called fumed SiO2. A further example of synthetically produced particulate amorphous silicon dioxide is silicon dioxide obtained by pyrolysis of ZrSiO4 to ZrO2 and SiO2, as described for example in DE 102012020509, and partial or substantially complete removal of ZrO2. As or in component (M3) according to the process of the invention, the use of synthetically produced particulate amorphous SiO2, more preferably fumed particulate amorphous SiO2 and / or SiO2 by pyrolysis of ZrSiO4, is preferred.Particulate amorphous silicon dioxide suitable for the purposes of the present invention are also described, for example, in DE 102004042535 A1, DE 102012020510 A1 and DE 102012020511 A1. The particulate amorphous silicon dioxide is preferably used in an amount in the range of 0.3 to 3.0% by weight, based on the total weight (total mass) of the molding material mixture (the sum of the weights or masses of components (M1), (M2) and, if present, (M3) and further optional components, respectively).

[0045] The barium sulfate used may be synthetically produced or may be in the form of natural barium sulfate, i.e., minerals containing barium sulfate, such as barite or barite. Synthetically produced barium sulfate (also called "precipitated barium sulfate") is produced, for example, by a precipitation reaction. For this purpose, a readily soluble barium compound (barium salt) is usually dissolved in water. The poorly soluble barium sulfate is then precipitated by the addition of a readily soluble sulfate salt (e.g. sodium sulfate) or sulfuric acid. The precipitated barium sulfate is separated by filtration, drying and may also be separated by grinding. Barium sulfate suitable for the purposes of the present invention is also described, for example, in DE 102012104934. Barium sulfate is preferably used in an amount ranging from 0.02 to 5.0% by weight, based on the total weight (total mass) of the molding material mixture (the sum of the weights or masses of the components (M1), (M2) and, if present, (M3) and further optional components, respectively).

[0046] The carbohydrates that can be used as or in the component (M3) of the above-mentioned inventive process are preferably selected from the group consisting of oligosaccharides and polysaccharides, preferably selected from the group consisting of cellulose, starch and dextrin. The carbohydrates mentioned can be used individually or in combination with one another. Carbohydrates suitable for the purposes of the present invention are also described, for example, in EP 2104580. The carbohydrate or carbohydrates are preferably used in an amount ranging from 0.01 to 10.0% by weight, based on the total weight (total mass) of the molding material mixture (the sum of the weights or masses of components (M1), (M2) and, if any, (M3) and further optional components).

[0047] The phosphorus compounds which can be used as or in the component (M3) of the above-mentioned inventive process are preferably selected from the group consisting of organic and inorganic phosphates, preferably from the group consisting of inorganic alkali metal phosphates. The phosphorus compounds mentioned can be used individually or in combination with one another. Phosphorus compounds suitable for the purposes of the present invention are also described, for example, in EP 2097192. The phosphorus compound or compounds are preferably used in an amount ranging from 0.05 to 1.0% by weight, based on the total weight (total mass) of the molding material mixture (the sum of the weights or masses of components (M1), (M2) and, if any, (M3) and further optional components).

[0048] The surface-active compounds which can be used as or in component (M3) in the above-mentioned inventive process are preferably selected from the group consisting of anionic surfactants, nonionic surfactants, cationic surfactants and amphoteric surfactants. The surfactants mentioned can be used individually or in combination with one another. Surfactants suitable for the purposes of the present invention are also described, for example, in DE 102007051850. The surface-active compound(s) or surface-active compounds(s) are preferably used in an amount ranging from 0.001 to 1.0% by weight, based on the total weight (total mass) of the molding material mixture (the sum of the weights or masses of components (M1), (M2) and, if present, (M3) and further optional components, respectively). The above-mentioned surface-active compounds can also be used as components of component (K1).

[0049] The boron oxide compounds which can be used as or in the component (M3) of the above-mentioned inventive process are preferably selected from the group consisting of borates, boric acid, boric anhydride, borosilicates, borophosphates and borophosphosilicate, more preferably from the group consisting of alkali metal borates and alkaline earth metal borates, the boron oxide compounds preferably not containing organic groups. The mentioned boron oxide compounds can be used individually or in combination with one another. Boron oxide compounds suitable for the purposes of the present invention are also described, for example, in DE 102013111626. The boron oxide compound or boron oxide compounds are preferably used in an amount ranging from 0.001 to 1.0% by weight, based on the total weight (total mass) of the molding material mixture (the sum of the weights or masses of components (M1), (M2) and, if any, (M3) and further optional components). The above-mentioned boron oxide compounds can also be used as components of component (K1).

[0050] Metal oxides which can be used as or in the component (M3) of the above-mentioned inventive process preferably comprise particulate mixed metal oxides, preferably comprising oxides of aluminum and / or oxides of zirconium. Preferred metal oxides comprise particulate aluminum oxides, preferably in the α-phase, and / or particulate aluminum / silicon mixed oxides without a layered silicate structure. The metal oxides mentioned can be used individually or in combination with one another. Metal oxides suitable for the purposes of the present invention are also described, for example, in DE 102012113074 and DE 102012113073. The metal oxide(s) or metal oxides are preferably used in an amount in the range of 0.05 to 8.0% by weight, based on the total weight (total mass) of the molding material mixture (the sum of the weights or masses of components (M1), (M2) and, if any, (M3) and further optional components). The lubricant that can be used as or in the component (M3) of the above-mentioned method of the invention is preferably selected from graphite and / or molybdenum(IV) sulfide. The lubricants mentioned can be used individually or in combination with each other. Lubricants suitable for the purposes of the invention are also described, for example, in WO 2014 / 202042. The lubricant or lubricants are preferably used in an amount ranging from 0.01 to 0.2% by weight based on the total weight (total mass) of the molding material mixture (the sum of the weight or mass of components (M1), (M2) and, if any, (M3) and further optional components, respectively).

[0051] Silanes that can be used as or in the component (M3) of the above-mentioned inventive process are preferably selected from the group consisting of aminosilanes, epoxysilanes, mercaptosilanes, hydroxysilanes and ureidosilanes. The silanes may also act as lubricants. The silanes mentioned can be used individually or in combination with one another. Silanes suitable for the purposes of the present invention are also described, for example, in WO 2014 / 202042. The silane or silanes are preferably used in an amount ranging from 0.1 to 2.0% by weight, based on the total weight (total mass) of the molding material mixture (the sum of the weights or masses of components (M1), (M2) and, if any, (M3) and further optional components).

[0052] The release agents which can be used as or in the component (M3) of the above-mentioned inventive process are preferably selected from the group consisting of calcium stearate, fatty acid esters, waxes, natural resins and alkyd resins. The release agents mentioned can be used individually or in combination with one another. Release agents suitable for the purposes of the present invention are also described, for example, in EP 1 802 409. The release agent(s) or release agents are preferably used in an amount ranging from 0.1 to 2.0% by weight, based on the total weight (total mass) of the molding material mixture (the sum of the weights or masses of components (M1), (M2) and, if any, (M3) and further optional components).

[0053] The ester(s) that can be used as or in the component (M3) of the above-mentioned method of the invention are preferably selected from the group consisting of intramolecular or intermolecular reaction products of alcohols and acids, the alcohols being selected from the group consisting of C1-C8 monoalcohols, C1-C8 dialcohols, preferably C2-C8 dialcohols, and C1-C8 trialcohols, preferably C3-C8 trialcohols, preferably selected from the group consisting of ethylene glycol, 1,2-propanediol and glycerol, and the acids being selected from the group consisting of organic C1-C8 monocarboxylic acids, preferably organic C2-C8 monocarboxylic acids, organic C2-C8 dicarboxylic acids, organic C2-C8 tricarboxylic acids, preferably organic C3-C8 tricarboxylic acids, and inorganic acids, preferably selected from the group consisting of formic acid, acetic acid, propionic acid, lactic acid, oxalic acid, succinic acid, malonic acid, phosphoric acid, sulfuric acid, boric acid and carbonic acid, and the at least one ester is preferably propylene carbonate or γ-butyrolactone. The esters can be used individually or in combination with one another. The ester or esters are preferably used in an amount ranging up to 0.4% by weight, preferably in an amount ranging from 0.01% to 0.4% by weight, based on the total weight (total mass) of the molding material mixture (the weight or mass sum of components (M1), (M2) and, if present, (M3) and further optional components, respectively).

[0054] Said one or more components (M3), particulate amorphous silicon dioxide; barium sulfate; carbohydrates; phosphorus compounds; surface active compounds; boron oxide compounds; metal oxides; lubricants, esters and release agents, can be used individually or in combination with each other. One or more components (M3) can be added, for example, individually or together, preferably together, to the mold base material (M1) and mixed with the latter, and then this premixture of components (M1) and (M3) can be mixed with the prepared (premixed) solution or dispersion (M2) and mixed therewith (preferably homogeneously). The premixture of components (M1) and (M3) can be mixed individually with further components (K1), (K2a), and (K2b) may also be mixed, and then the resulting molding material mixture can be mixed (preferably homogeneously). The water-soluble components (M3), preferably the surface-active compounds and / or the boron oxide compounds, can for example be added individually or together to component (K1) and / or may be part of component (K1). Furthermore, the above-mentioned methods of the invention (especially those expressed as preferred above or below) are also preferred, in which the first water-glass-free solution or dispersion (K2a) comprises lithium hydroxide dissolved in water and the second water-glass-free solution or dispersion (K2b) (if present or used) may also comprise lithium hydroxide dissolved in water.

[0055] It is therefore preferred that the first water-glass-free solution or dispersion (K2a) containing lithium ions dissolved in water contains lithium hydroxide dissolved in water. If the second water-glass-free solution or dispersion (K2b) containing alkali metal ions dissolved in water contains lithium ions, it is therefore also preferred that the second water-glass-free solution or dispersion contains lithium hydroxide dissolved in water. Lithium hydroxide, in particular lithium hydroxide monohydrate, has a suitable water solubility for the purposes of the present invention. In-house trials have furthermore shown that solutions and / or dispersions (K2a) and / or (K2b) with very suitable storage stability can be produced for the purposes of the present invention using lithium hydroxide, in particular lithium hydroxide monohydrate. The lithium ion-containing components (K2a) and / or (K2b) are therefore preferably produced using lithium hydroxide, more preferably lithium hydroxide monohydrate.

[0056] the aqueous solution or dispersion (K1) comprising water glass has a pH in the range from 10.0 to 13.0, preferably in the range from 11.0 to 12.5, And / or (preferably "and") the first waterglass-free solution or dispersion (K2a) containing lithium ions dissolved in water has a pH in the range from 8.0 to 14.0, preferably in the range from 11.5 to 13.5, and / or (preferably "and" when component (K2b) is present) the second waterglass-free solution or dispersion (K2b), if used, containing lithium ions dissolved in water, has a pH in the range from 8.0 to 14.0, preferably in the range from 11.5 to 13.5, Also preferred are the methods of the invention described above, particularly those methods of the invention which are referred to as preferred in the text.

[0057] The present invention comprises the following separate components: (K1) the SiO2 content is in the range of 20 to 34% by weight, preferably in the range of 25 to 34% by weight, based on the total weight of the solution or dispersion, and / or the SiO2 / MO molar ratio is greater than that of the lithium-containing water glass produced; an aqueous solution or dispersion containing water glass; and (K2a) The concentration of lithium ions is in the range of 0.3 to 5.3 mol / L, preferably in the range of 1.0 to 5.0 mol / L; The total concentration of lithium, sodium and potassium ions is in the range of 0.3 to 28.0 mol / L, preferably in the range of 0.3 to 20.0 mol / L, and more preferably in the range of 1.0 to 10.0 mol / L. A first water glass-free solution or dispersion containing lithium ions dissolved in water. At least The invention also relates to a kit for producing a solution or dispersion comprising lithium-containing waterglass.

[0058] As a further separate component, (K2b) The concentration of lithium ions is lower than that of component (K2a), preferably in the range of 0 to 5.0 mol / L, more preferably in the range of 0 to 2.0 mol / L; the total concentration of lithium, sodium and potassium ions is in the range of 0.3 to 28.0 mol / L, preferably in the range of 0.3 to 20.0 mol / L, and more preferably in the range of 1.0 to 10.0 mol / L; Preferably, the total concentration of lithium, sodium and potassium ions differs from the total concentration of lithium, sodium and potassium ions in component (K2a) by no more than 20%, preferably no more than 10%. A second water glass-free solution or dispersion containing alkali metal ions dissolved in water. Also includes The kit of the invention described above is particularly preferred. In a preferred embodiment of the kit of the present invention or a kit more preferred according to the present invention, the concentration of lithium ions in component (K2b) is lower than that in component (K2a), and is preferably in the range of 0.1 to 5.0 mol / L, more preferably in the range of 0.1 to 2.0 mol / L.

[0059] The following separate components: (K1) the SiO2 content is in the range of 20 to 34% by weight, preferably in the range of 25 to 34% by weight, based on the total weight of the solution or dispersion, and / or the SiO2 / MO molar ratio is greater than the molar ratio of the lithium-containing water glass being produced; an aqueous solution or dispersion containing water glass; (K2a) The concentration of lithium ions is in the range of 0.3 to 5.3 mol / L, preferably in the range of 1.0 to 5.0 mol / L; The total concentration of lithium, sodium and potassium ions is in the range of 0.3 to 28.0 mol / L, preferably in the range of 0.3 to 20.0 mol / L, and more preferably in the range of 1.0 to 10.0 mol / L. a first water glass-free solution or dispersion comprising lithium ions dissolved in water; and (K2b) The concentration of lithium ions is lower than that of component (K2a), preferably in the range of 0.1 to 5.0 mol / L, more preferably in the range of 0.1 to 2.0 mol / L; the total concentration of lithium, sodium and potassium ions is in the range of 0.3 to 28.0 mol / L, preferably in the range of 0.3 to 20.0 mol / L, and more preferably in the range of 1.0 to 10.0 mol / L; Preferably, the total concentration of lithium, sodium and potassium ions differs from the total concentration of lithium, sodium and potassium ions in component (K2a) by no more than 20%, preferably no more than 10%. A second water glass-free solution or dispersion containing lithium ions dissolved in water. Particularly preferred are the above-mentioned inventive kits (especially those mentioned above or below as being preferred), which comprise at least With regard to the further preferred embodiments of the kit of the invention, the explanations specified above for the method of the invention are correspondingly valid and vice versa. The above specified kits of the invention are suitable and intended for use in the above specified methods of the invention.

[0060] The invention also relates to a molding material mixture comprising (M1) Mold base material and (M2) has a SiO2 / M2O molar ratio in the range of 1.6 to 3.5, preferably in the range of 1.8 to 3.0; The mole fraction of Li2O in M2O is in the range of 0.05 to 0.60, preferably in the range of 0.1 to 0.4. Solution or dispersion containing lithium-containing water glass The present invention relates to the use of the above-mentioned kit of the invention or the preferred kit of the invention for producing a molding material mixture or for producing a molding material mixture and a molding thereof, which comprises With regard to the preferred embodiments of the use according to the invention, the explanations specified above for the method according to the invention and the kit according to the invention are correspondingly valid.

[0061] The present invention further comprises: The device, - a first storage tank (Z1) containing an aqueous solution or dispersion (K1) comprising water glass as a first component, the SiO2 content of which is in the range from 20 to 34% by weight, preferably in the range from 25 to 34% by weight, based on the total weight of the solution or dispersion, and / or the SiO2 / M2O molar ratio is greater than the molar ratio of the lithium-containing water glass in the molding material mixture being produced, - The concentration of lithium ions is in the range of 0.3 to 5.3 mol / L, preferably in the range of 1.0 to 5.0 mol / L; The total concentration of lithium, sodium and potassium ions is in the range of 0.3 to 28.0 mol / L, preferably in the range of 0.3 to 20.0 mol / L, and more preferably in the range of 1.0 to 10.0 mol / L. a second storage tank (Z2) containing as a second component a first water-glass-free solution or dispersion (K2a) comprising lithium ions dissolved in water, - preferably a mixing installation (Z3), more preferably a mixing tube, very preferably a static mixing pipe, for mixing at least the first and second components to produce an intermediate solution or dispersion (said or unspecified) (in the context of the method of the invention, this intermediate solution or dispersion is identified as (M2)); At least - preferably at least a first and a second storage tank are in each case connected to the mixing installation (Z3) by one or more lines (Z4), MO represents in each case the total amount of lithium oxide, sodium oxide and potassium oxide; and / or the lithium-containing water glass in the intermediate solution or dispersion has a SiO2 / M2O molar ratio in the range from 1.6 to 3.5, preferably in the range from 1.8 to 3.0, and / or the molar fraction of Li2O in M2O is in the range from 0.05 to 0.60, preferably in the range from 0.1 to 0.4, M2O representing in each case the total amount of lithium oxide, sodium oxide and potassium oxide, and / or - the use takes place in a method according to the invention as defined above (in particular the methods mentioned above or below as being preferred), It also relates to an apparatus for producing intermediate solutions or dispersions comprising lithium-containing water glass for use in the production of molding material mixtures or for producing molding material mixtures and shaped bodies thereof (preferably for use in the production by the method of the invention), preferably for use in the production of molding material mixtures or for producing molding material mixtures and shaped bodies thereof.

[0062] The inventive apparatus preferably comprises a mixing facility (Z3), and preferably at least the first and second storage tanks are in each case connected to the mixing facility (Z3) by one or more lines (Z4). In this preferred embodiment, the inventive apparatus is an apparatus for producing an intermediate solution or dispersion comprising lithium-containing water glass for use in the production of molding material mixtures or for producing molding material mixtures and their shaped bodies (in the context of the inventive process, this intermediate solution or dispersion is referred to as (M2)).

[0063] However, the invention also includes an apparatus as described above in which one can do without a mixing facility and the components (K1), (K2a) and - if present and used - (K2b) are passed directly into the mould base material (M1) and only there do they become mixed with each other and with the mould base material (M1).

[0064] The mixing facility (Z3) may at the same time be a storage tank ((Z1), (Z2) or (Z5); see below). The contents of the storage tank or tanks can be conveyed to the mixing facility by one or more pumps. Components (K1), (K2a) and (K2b) can also be premixed in only one of the storage tanks provided and then mixed with the mould base material. It is also possible to premix only component (K1) with (K2a), or (K1) with (K2b), or (K2a) with (K2b) in the storage tank and only then mix with the third component (respectively (K2b) or (K2a) or (K1)). It is also possible to mix each of components (K1), (K2a) and (K2b) directly with the mould base material without mixing with any of the other components. With regard to the preferred embodiments of the device of the invention, the explanations specified above for the method of the invention, the kit of the invention and the use according to the invention are correspondingly valid and vice versa. The devices of the invention as specified above or below are suitable and intended for use in the above specified methods of the invention. The kits of the invention as specified above are suitable and intended for use with the devices as specified above or below.

[0065] The device of the present invention is further preferably - the concentration of lithium ions is lower than that of component (K2a), preferably in the range of 0 to 5.0 mol / L, more preferably in the range of 0 to 2.0 mol / L; The total concentration of lithium, sodium and potassium ions is in the range of 0.3 to 28.0 mol / L, preferably in the range of 0.3 to 20.0 mol / L, and more preferably in the range of 1.0 to 10.0 mol / L; Preferably, the total concentration of lithium, sodium and potassium ions differs from the total concentration of lithium, sodium and potassium ions in component (K2a) by no more than 20%, preferably no more than 10%; a third storage tank (Z5) containing a second water glass-free solution or dispersion (K2b) containing alkali metal ions dissolved in water; Further comprising: Preferably, a mixing facility (Z3) is implemented to mix at least the first, second and third components to produce an intermediate solution or dispersion, and Preferably at least a first, a second and a third storage tank are connected to the mixing installation (Z3) in each case by one or more lines (Z4).

[0066] In a preferred embodiment of the device of the invention, or of the preferred device according to the invention, the concentration of lithium ions in component (K2b) in the third storage tank (Z5) is lower than in component (K2a), preferably in the range of 0.1 to 5.0 mol / L, more preferably in the range of 0.1 to 2.0 mol / L. The invention will be described in more detail below in the examples specified below and with reference to the drawings. [Brief description of the drawings]

[0067] [Figure 1]FIG. 1 shows a schematic structure of a detailed apparatus of the invention having the following components of the apparatus: a first storage tank (Z1), a second storage tank (Z2), a mixing facility (Z3), and one or more (in this case multiple) lines (Z4) connecting the first and second storage tanks to the mixing facility. [Diagram 2] FIG. 2 shows a schematic structure of a detailed apparatus of the invention having the following components of the apparatus: a first storage tank (Z1), a second storage tank (Z2), a mixing facility (Z3) (in this case identical to the first storage tank (Z1)), and one or more (in this case one) lines (Z4) connecting the first and second storage tanks to the mixing facility (the first storage tank and the mixing facility are identical). [Diagram 3] FIG. 3 shows a schematic structure of a detailed apparatus of the invention having the following components of the apparatus: a first storage tank (Z1), a second storage tank (Z2), a third storage tank (Z5), a mixing facility (Z3), and one or more (in this case multiple) lines (Z4) connecting the first, second and third storage tanks to the mixing facility. EXAMPLES

[0068] The examples are intended to describe and explain the invention in more detail without limiting its scope of protection. Unless otherwise stated, work was carried out under normal laboratory conditions (25° C., standard pressure).

[0069] (Example 1a) Exemplary components (K1), (K2a) and (K2b) Exemplary components (K1), (K2a) and (K2b), having the properties shown in Table 1a, were prepared by conventional methods.

[0070] TIFF0007631418000001.tif62144 In Table 1a, "c(Li + ) represents the concentration of lithium ions, and "c(Li + / Na + / K +) denotes the total concentration of lithium, sodium and potassium ions. "ns" means that no value is stated for the cell in question. The figures "% by weight" are based on the total weight of the corresponding components (K1), (K2a) or (K2b) in each case.

[0071] (Example 1b) Determination of pH of components (K1), (K2a) and (K2b) The preferred components (K1), (K2a) and (K2b) were prepared in the usual manner. The pH values ​​of the preferred components were then determined in the usual manner. The results are shown in Table 1b below.

[0072] TIFF0007631418000002.tif21133 The other properties of the preferred components (K1), (K2a) and (K2b) are very similar to those in Table 1a. There are no significant deviations.

[0073] (Example 2) Preparation of the solution or dispersion containing the lithium-containing water glass of the present invention An exemplary solution or dispersion (M2) containing lithium-containing water glass is prepared according to the method of the invention in the usual way by mixing components (K1), (K2a) with one another and also (K2b). The components used are in each case those specified in Example 1. For this purpose, the respective proportions of component (K1) are introduced first, the respective proportions of component (K2a) are added, and optionally also (K2b). The resulting solution or dispersion (M2) is homogenized by shaking or stirring. The results are shown in Table 2.

[0074] TIFF0007631418000003.tif99139

[0075] (Example 3) Production of molding material mixture Molding material mixtures were produced according to the inventive method (molding material mixtures EF1 to EF3) and a comparative molding material mixture (VF1) according to a conventional, non-inventive method from the components shown in Table 4 according to the protocol shown below. All amounts in Table 4 are given in parts by weight.

[0076] The "binders" used (see Table 4) comprised a solution or dispersion (M2) containing lithium-containing water glass according to the invention, produced according to Table 3, and a non-inventive solution or dispersion (M2v) respectively (see binders EL1 to EL3 and VL1). The "mould base material" (M1) used in each case was quartz sand (H31 from Quarzwerke GmbH, Frechen). The "additive" used in each case was the commercially available powdered additive for moulding, Anorgit® 8610 (from Huttenes-Albertus Chemische Werke Gesellschaft mit beschrankter Haftung). Its constituents include particulate amorphous silicon dioxide.

[0077] TIFF0007631418000004.tif47144

[0078] TIFF0007631418000005.tif41124 The components of the molding material mixture were mixed in a laboratory paddle mixer (Multiserw). For this purpose, the silica sand was introduced first, followed by the powdered additives and mixing. Afterwards, the premixed binder (see Table 3) was added. The mixture was then stirred for a total of 2 minutes. The resulting molding material mixtures were then used respectively for the following investigations.

[0079] (Example 4) Manufacturing of molded bodies The molding material mixture prepared in Example 3 (see Table 4) was used to produce moldings (test pieces, i.e. standard bending test bars with dimensions 22.4 mm x 22.4 mm x 165 mm) using a heatable mold for producing bending test pieces (shown in the March 1974 M11 Merkblatt of the Verein deutscher GieBereifachleute), which were used for the following experiments.

[0080] The molding material mixtures were each introduced into the mold (core temperature 180° C.) by compressed air (4 bar). The injection time was 3 seconds, followed by a curing time of 30 seconds (delay time 3 seconds). To accelerate the curing of the mixtures, hot air (gas pressure: 2 bar, gas and gas hose temperature: 180° C.) was passed through the mold during the curing time of 30 seconds. The test specimens produced correspond to bodies which can be used in the foundry industry, for example as models of moulds or cores, as is common in the technical field.

[0081] (Example 5) Storage stability of molded products The storage stability of water glass bonded moldings depends on the ambient conditions, especially on the air humidity. The higher the humidity, the greater the risk of damage to the moldings (e.g. core damage). Damage to the moldings is evident, for example, in part failure (e.g. core destruction) or a large reduction in strength (lower residual strength compared to cold strength). In the case of high humidity, there is also water uptake, which can cause gas defects in the casting (e.g. air bubbles in the casting). The investigations were carried out under defined conditions (temperature and relative humidity) and in each case monitored by a data logger. The mouldings (test specimens) are each characterised in Table 5 (see column "Experimental") by the moulding material mixture used to produce them (see Example 3 and Table 3).

[0082] 5.1. Determining the time of component failure For the determination of the time to part failure (fracture of the test specimen), the test specimens were stored in a conditioned cabinet and the time to failure was observed, the respective times (hours) being given in Table 5 as the average of three measurements in each case. 5.2. Determination of the residual strength of the test specimen The retained strength was determined by storing the test specimens in a conditioned cabinet for a defined period of time (see Table 5), and then measuring the flexural strength immediately after removal from the conditioned cabinet.

[0083] The bending strength was determined by mounting the test specimens prepared in Example 4 on a Georg-Fischer strength tester (Multiserw) equipped with a three-point bending apparatus and measuring the force that caused the test specimen to break. The bending strength was measured after the periods shown in Table 5. The moldings (test specimens) are each characterized in Table 5 (see the "Experimental" column) by the molding material mixture (see Example 3 and Table 4) used to prepare them. The measurements obtained (residual strength expressed as a percentage of the original value) are given in Table 5 as the average of three measurements in each case.

[0084] 5.3. Determination of moisture absorption of test specimens To determine moisture absorption, the specimens were weighed 1 hour after removal from the mold and then stored in a conditioned cabinet for a given time (see Table 5). The specimens were weighed again immediately after removal from the conditioned cabinet. The resulting weight difference (or mass difference) (%) is shown in Table 5 as the average of the three measurements.

[0085] TIFF0007631418000006.tif62149 In Table 5, "rh" means relative humidity and "nd" means "not determined" (i.e., the measurement was not determined). 3 ", 35.3g / m 3 ", 14.7g / m 3 " and "25.0 g / m 3 " indicates the absolute humidity in each case.

[0086] From the measurements reported in Table 5, it is clear that the mouldings produced by the method of the invention using lithium-containing water glass (test pieces EF1, EF2 and EF3) show better storage stability than the comparative test piece (VF1) produced by a non-inventive method (no lithium added). The mouldings produced according to the invention showed better storage capacity (see Table 5, column "Time to part failure"), higher residual strength after storage (see Table 5, column "Residual strength at 35°C") and lower water absorption (see Table 5, column "Water absorption") than the comparative mouldings not produced according to the invention. It is further evident from Table 5 that as the lithium ion content of the solution or dispersion (M2) used to prepare the compacts is increased within the stated ranges, improvements are observed in the storage stability (higher), residual strength (higher) and water absorption (lower) properties of the compacts. Higher water absorption in that part of the compact has the general effect of increasing the risk of gas evolution during the casting operation and therefore of a deterioration in the quality of the casting due to the entrapment of gas bubbles.

[0087] The conclusion that can be drawn from these observations is that a lithium ion concentration in the solution or dispersion (M2) to be prepared (which is possible using the method of the invention and / or the kit of the invention) that can be correspondingly flexibly adjusted at the place of use of the method of the invention and / or the kit of the invention and / or the device of the invention, respectively, depending on the prevailing climatic conditions (in particular the ambient temperature and the relative and / or absolute humidity), is advantageous, since this makes it possible to establish and / or control in a targeted manner the desired shaped body properties, in particular the desired storage properties of the shaped bodies combined with the binder.

[0088] For example, it is possible to reduce the lithium ion content in the solution or dispersion (M2) when the relevant climatic conditions do not require this, i.e. as long as less severe relevant climatic conditions prevail, especially at relatively low humidity, and thus save money. This cost saving has become even more important recently, since lithium compounds have become rather expensive, mainly due to the increasing demand in the battery industry.

[0089] 5.4. Effect of storage period of solution or dispersion (M2) on storage stability of molded bodies The components (K1), (K2a) and (K2b) of the solution or dispersion (M2) were used and mixed with each other or with each other and with the mould base material (M1) in the manner described below and under otherwise constant conditions. a) Components (K1), (K2a) and (K2b) were mixed directly with the mould base material without premixing. b) Components (K1), (K2a) and (K2b) were premixed and then the premix was mixed directly with the mold base material. c) Components (K1), (K2a) and (K2b) were premixed and the premix was mixed directly with the mould base material one day after its preparation. d) Components (K1), (K2a) and (K2b) were premixed and the premix was mixed directly with the mould base material 2 days after its preparation. e) Components (K1), (K2a) and (K2b) were premixed and the premix was mixed directly with the mould base material 3 days after its preparation. Next, the molding material mixtures a) to e) obtained above were used to produce moldings (test pieces; see Example 4) as described above, and their storage stability was investigated ("time to part failure"; see Example 5.1). When the storage stability of molded articles (test pieces) produced by the method of the present invention using the above molding material mixtures a) to e) was measured, no significant difference was observed. From this result it is possible to conclude that the solution or dispersion (M2) produced by the method of the invention can be stored for at least 3 days under the test conditions without any performance-related deterioration.

[0090] (Example 6) Investigating the storage stability of the solution or dispersion (M2) Samples of the solution or dispersion (M2) prepared in Example 3 (designated "EL3") were stored in closed containers under the conditions specified in Table 6 and their quality and consistency at the times indicated in Table 6 were in each case determined by testing, the results of which are also shown in Table 6.

[0091] TIFF0007631418000007.tif36138

[0092] In table 6, the symbols have the following meaning: "++": no changes in the solution or dispersion (M2) are observed; "+": slight changes in the solution or dispersion (M2) are observed, no adverse effects on the quality; "o": slight gelling is detectable, the solution or dispersion (M2) is still suitable for use without adverse effects; "-": considerable precipitation is visible, the solution or dispersion (M2) is no longer suitable for use without adverse effects (e.g. in pumps, filters, metering units). From the above results it is clear that the solution or dispersion (M2) produced by the method of the invention can be used for up to 8 days (preferably up to 7 days) even under adverse storage conditions without its quality deteriorating to an extent relevant for implementation in the foundry industry for the production of shaped bodies.

[0093] Thus, as is also evident from Table 6, the solutions or dispersions (M2) produced with the advantageous (high) lithium contents can be stored and used in industrial practice in premixed form for the short term or at most the medium term. However, for long-term storage (e.g. several weeks), homogeneous (e.g. premixed) solutions or dispersions (M2) with the advantageous (high) lithium contents are not suitable for the reasons given above.

[0094] Therefore, according to the subject matter of the present invention, the separately stored components (K1), (K2a) and also (K2b) should not be mixed with one another or with a mould base material to produce a moulding material mixture, until a short or medium period before the actual industrial deployment of such solutions or dispersions (M2) having an advantageous (high) lithium content.

Claims

1. A method for producing a molding material mixture, comprising the steps of: (M1) Mold base material and (M2) SiO in the range of 1.6 to 3.5 2 / M 2 O molar ratio, M 2 Li in O 2 The mole fraction of O is in the range of 0.05 to 0.60; Solution or dispersion containing lithium-containing water glass Including, Steps below (1) The following separate components (K1) and (K2a): (K1) SiO 2 The content is in the range of 20 to 34% by weight, based on the total weight of the solution or dispersion; An aqueous solution or dispersion containing water glass, Aqueous solution or dispersion containing water glass having a pH in the range of 10.0 to 13.0 and (K2a) The concentration of lithium ions is in the range of 0.3 to 5.3 mol / L; The total concentration of lithium, sodium and potassium ions is in the range of 0.3 to 28.0 mol / L; A first solution or a first dispersion containing lithium ions dissolved in water, the first solution or dispersion being free of water glass, A first waterglass-free solution or dispersion comprising lithium ions dissolved in water, the solution or dispersion having a pH in the range of 8.0 to 14.

0. Producing or providing a kit comprising at least And then (2) preparing a mixture of the mold base material (M1) with a portion of component (K1) and with a portion of component (K2a), forming a solution or dispersion (M2) by mixing together the components of the kit used; Including, M 2 O represents the total amount of lithium oxide, sodium oxide, and potassium oxide; The solution or dispersion (M2) produced does not contain visible precipitates or gel parts before the formation of the mixture with the mold base material (M1); method.

2. The method according to claim 1, wherein the SiO 2 / M 2 O molar ratio of component (K1) is greater than the SiO 2 / M 2 O molar ratio of the lithium-containing water glass in the molding material mixture produced.

3. The kit produced or provided in step (1) further comprises the following component (K2b): (K2b) The concentration of lithium ions is lower than that in component (K2a); The total concentration of lithium, sodium and potassium ions is in the range of 0.3 to 28.0 mol / L; a second solution or dispersion free of water glass, comprising alkali metal ions dissolved in water; Further comprising: The step (2) includes the following steps: Producing a mixture of the mould base material (M1), a portion of component (K1) and a portion of component (K2a) or a mixture of the mould base material (M1), a portion of component (K1), a portion of component (K2a) and a portion of component (K2b), forming a solution or dispersion (M2) by mixing together the components of the kit used. Including, The method according to claim 1 or 2.

4. A method according to any one of claims 1 to 3, wherein the total concentration of lithium, sodium and potassium ions in component (K2b) differs from the total concentration of lithium, sodium and potassium ions in component (K2a) by 20% or less.

5. The molding material mixture is (M1) Mold base material and (M2) SiO in the range of 1.6 to 3.5 2 / M 2 O molar ratio, M 2 Li in O 2 The mole fraction of O is in the range of 0.05 to 0.60; Solution or dispersion containing lithium-containing water glass Including, Steps below (1) The following separate components (K1), (K2a) and (K2b): (K1) SiO 2 The content is in the range of 20 to 34% by weight, based on the total weight of the solution or dispersion; an aqueous solution or dispersion containing water glass; (K2a) The concentration of lithium ions is in the range of 0.3 to 5.3 mol / L; The total concentration of lithium, sodium and potassium ions is in the range of 0.3 to 28.0 mol / L; a first water glass-free solution or dispersion comprising lithium ions dissolved in water; and (K2b) The concentration of lithium ions is lower than that in component (K2a) and is in the range of 0.1 to 5.0 mol / L; The total concentration of lithium, sodium and potassium ions is in the range of 0.3 to 28.0 mol / L; A second water glass-free solution or dispersion containing lithium ions dissolved in water. Producing or providing a kit comprising at least And then (2) preparing a mixture of the mould base material (M1) with a part of component (K1), with a part of component (K2a) and with a part of component (K2b), and mixing together the components of the kit used to form a solution or dispersion (M2); Including, M 2 O represents the total amount of lithium oxide, sodium oxide and potassium oxide; 5. The method according to any one of claims 1 to 4.

6. The method according to claim 5, wherein the SiO 2 / M 2 O molar ratio of component (K1) is greater than the molar ratio of the lithium-containing waterglass in the molding material mixture produced.

7. The method according to claim 5 or 6, wherein the total concentration of lithium, sodium and potassium ions in component (K2b) differs from the total concentration of lithium, sodium and potassium ions in component (K2a) by 20% or less.

8. Additional steps - establishing, determining or estimating one or more parameters selected from the group consisting of: ambient temperature during the production of the shaped body, relative humidity during the production of the shaped body, temperature during storage of the shaped body, relative humidity during storage of the shaped body, absolute humidity during the production of the shaped body, absolute humidity during storage of the shaped body and storage time of the shaped body, and - controlling the proportions of components (K2a) and (K2b) to be used as a function of an established, determined or estimated parameter or parameters selected from the group consisting of the ambient temperature during the production of the shaped bodies, the relative humidity during the production of the shaped bodies, the temperature during the storage of the shaped bodies, the relative humidity during the storage of the shaped bodies, the absolute humidity during the production of the shaped bodies, the absolute humidity during the storage of the shaped bodies and the storage period of the shaped bodies. The method according to any one of claims 1 to 7, comprising:

9. It is carried out as an at least partially continuous production of several shaped bodies, (A) when one or more parameters selected from the group consisting of ambient temperature during production of the molded body, relative humidity during production of the molded body, temperature during storage of the molded body, relative humidity during storage of the molded body, absolute humidity during production of the molded body, absolute humidity during storage of the molded body, and storage period of the molded body increase or are expected to increase; - for the production of shaped bodies, the proportion of component (K2a) used is increased or for the production of shaped bodies, the proportion of M in the solution or dispersion (M2) is increased. 2 Li in O 2 increasing the mole fraction of O; or for the production of moldings, the proportion of component (K2a) used is increased, and In order to produce the shaped bodies, the molar fraction of Li 2 O in M ​​2 O in the solution or dispersion (M2) is increased, or (B) when one or more parameters selected from the group consisting of ambient temperature during production of the molded body, relative humidity during production of the molded body, temperature during storage of the molded body, relative humidity during storage of the molded body, absolute humidity during production of the molded body, absolute humidity during storage of the molded body, and storage time of the molded body are decreased or decreased or are expected to decrease; - either reducing the proportion of component (K2a) used in the production of the article or increasing the proportion of component (K2b) used in the production of the article, or both, or - reducing the molar fraction of Li 2 O in M ​​2 O in the solution or dispersion (M2) for the production of shaped bodies, 9. The method according to any one of claims 1 to 8.

10. data collection or processing equipment is provided to establish, determine or estimate one or more parameters selected from the group consisting of: ambient temperature during production of the molded body, relative humidity during production of the molded body, temperature during storage of the molded body, relative humidity during storage of the molded body, absolute humidity during production of the molded body, absolute humidity during storage of the molded body, and storage time of the molded body; a control facility is provided for controlling the proportions of components (K2a) and (K2b) to be used as a function of the established, determined or estimated parameter or parameters; a data connection is established between the data acquisition or processing equipment and the control equipment for transferring parameter data; 10. The method according to any one of claims 5 to 9.

11. During the preparation of the molding compound mixture, (M3) Particulate, amorphous silicon dioxide; barium sulfate; carbohydrates; phosphorus compounds; surface active compounds; boron oxide compounds; metal oxides; lubricants, esters and release agents. One or more components selected from the group consisting of:

11. The method according to any one of claims 1 to 10.

12. The first water glass-free solution or dispersion (K2a) contains lithium hydroxide dissolved in water, and the second water glass-free solution or dispersion (K2b) contains lithium hydroxide dissolved in water; or 12. The method according to claim 3, wherein the first water-glass-free solution or dispersion (K2a) comprises lithium hydroxide dissolved in water and the second water-glass-free solution or dispersion (K2b) does not comprise lithium hydroxide dissolved in water.

13. the aqueous solution or dispersion (K1) containing water glass has a pH in the range from 11.0 to 12.5, or the first waterglass-free solution or dispersion (K2a) containing lithium ions dissolved in water has a pH in the range from 11.5 to 13.5, or the second waterglass-free solution or dispersion (K2b) containing lithium ions dissolved in water has a pH in the range from 8.0 to 14.0, 13. The method according to any one of claims 1 to 12.

14. In step (2), when no mould base material is present, a solution or dispersion (M2) is first formed by mixing together the components of the kit used, and then a mixture is formed of the mould base material (M1) or a part of it with a part or the total amount of the resulting solution or dispersion (M2).

14. The method according to any one of claims 1 to 13.

15. 15. The method according to claim 14, wherein in a mixing facility the components of the kit used are mixed together to form a solution or dispersion (M2).

16. 16. The method according to claim 14 or 15, wherein a part or the total amount of the solution or dispersion (M2) formed is stored in the mixing facility for a period of not more than 2 days before forming a mixture with the mould base material (M1) or a part thereof.

17. The method according to claim 1, further comprising the step of producing a molded body from the molding material mixture.

Citation Information

Patent Citations

  • Inorganic adhesive for warm box as well as preparation method and application of inorganic adhesive

    CN104907485A

  • Core sand or foundry sand, method for manufacturing core sand or foundry sand, method for manufacturing mold components, mold components, method for using core sand or foundry sand, and core manufacturing tools.

    JP2012501850A

  • A mold material mixture based on an inorganic binder, and a method for manufacturing molds and cores for metal casting.

    JP2015532209A

  • Method for producing lithium-containing mold material mixtures based on inorganic binders for producing molds and cores for metal casting; method for producing lithium-containing inorganic binders and casting molds or cores

    JP2016523183A

  • Method for manufacturing molds and cores for metal casting using carbonyl compounds, and molds and cores manufactured by said methods

    JP2017501885A